Dravet syndrome patient‐derived neurons suggest a novel epilepsy mechanism. Issue 1 (2nd July 2013) - Liu, Yu; Lopez‐Santiago, Luis F.; Yuan, Yukun; Jones, Julie M.; Zhang, Helen; O'Malley, Heather A.; Patino, Gustavo A.; O'Brien, Janelle E.; Rusconi, Raffaella; Gupta, Ajay; Thompson, Robert C.; Natowicz, Marvin R.; et al.
<x xml:space="preserve">Abstract</x> Objective Neuronal channelopathies cause brain disorders, including epilepsy, migraine, and ataxia. Despite the development of mouse models, pathophysiological mechanisms for these disorders remain uncertain. One particularly devastating channelopathy is Dravet syndrome (DS), a severe childhood epilepsy typically caused by de novo dominant mutations in the SCN1A gene encoding the voltage‐gated sodium channel Nav1.1. Heterologous expression of mutant channels suggests loss of function, raising the quandary of how loss of sodium channels underlying action potentials produces hyperexcitability. Mouse model studies suggest that decreased Nav1.1 function in interneurons causes disinhibition. We aim to determine how mutant SCN1A affects human neurons using the induced pluripotent stem cell (iPSC) method to generate patient‐specific neurons. Methods Here we derive forebrain‐like pyramidal‐ and bipolar‐shaped neurons from 2 DS subjects and 3 human controls by iPSC reprogramming of fibroblasts. DS and control iPSC‐derived neurons are compared using whole‐cell patch clamp recordings. Sodium current density and intrinsic neuronal excitability are examined. Results Neural progenitors from DS and human control iPSCs display a forebrain identity and differentiate into bipolar‐ and pyramidal‐shaped neurons. DS patient‐derived neurons show increased sodium currents in both bipolar‐ and pyramidal‐shaped neurons. Consistent with increased sodium currents, both types of patient‐derived neurons show spontaneous bursting and other evidence of hyperexcitability. Sodium channel transcripts are not elevated, consistent with a post‐translational mechanism. Interpretation These data demonstrate that epilepsy patient–specific iPSC‐derived neurons are useful for modeling epileptic‐like hyperactivity. Our findings reveal a previously unrecognized cell‐autonomous epilepsy mechanism potentially underlying DS, and offer a platform for screening new antiepileptic therapies. Ann Neurol 2013;74:128–139